Economic impact of COVID-19 pandemic on dairy sector: A meta-analysis - ABHIJIT DAS; MUNIANDY SIVARAM; THEJESH S (Indian Journal of Animal Sciences, 2021)
The novel coronavirus discovered in Wuhan city of China has spread across the world and World Health Organization (WHO) declared it as pandemic. This pandemic has negatively impacted every sector of the economy including dairy sector. In this article, an attempt was made to undertake meta-analysis to assess the economic impact of COVID-19 pandemic on dairy sector with 71 published articles. About 30% of the authors reported that the limited availability of dairy inputs was the major issue for dairy farmers during pandemic followed by reduction in farm gate prices, unsold milk, increased input prices, reduction in milk production, decreased demand for milk and inferior milk quality. Only 3% of authors found that there was no impact of pandemic on dairy farmers. In case of dairy industries and dairy cooperatives, 40% reported that disruption of demand for dairy products was the major issue followed by difficulty in transportation of dairy products, labour issues, increase in inventory cost and decline in revenue. From consumption point of view, 36% of literature reported that people consumed more dairy products during pandemic followed by changes in consumption preferences, panic buying, increased milk prices and less availability of dairy products. Dairy international trade was also affected severely due to movement restrictions. The recommendations to minimize the financial loss to various stakeholders of dairy sector include availability of dairy inputs at subsidised rates, increasing procurement prices of milk, high-tech backend infrastructure, encourage domestic consumption and export of dairy products.